2003
DOI: 10.1086/377644
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of 675 Group AStreptococcusIsolates Collected in a Carrier Study at Lackland Air Force Base, San Antonio, Texas

Abstract: Contemporary molecular genetic analysis methods have not been used to study large samples of carriage isolates of group A Streptococcus. To determine the emm types causing asymptomatic carriage and pharyngitis in a closed population, we analyzed 675 isolates recovered from a population-based surveillance study of 10,634 recruits at Lackland Air Force Base, Texas, during 4 months in 1993-1994. Strains with emm1 and emm6 alleles accounted for only 22% of the isolates recovered from asymptomatic recruits at entra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…GAs strains known to be highly pathogenic in mice and monkeys caused significantly lower survival and had significantly lower LD 50 s in wax worms than GAs strains associated with attenuated virulence or asymptomatic carriage. Furthermore, isogenic inactivation of proven virulence factors resulted in a significantly increased LD 50 and decreased lesion size compared to the wild-type strain, a finding that also strongly correlates with animal studies. Importantly, survival analysis and LD 50 determination in wax worms supported our hypothesis that a newly emerged GAs subclone that is epidemiologically associated with more human necrotizing fasciitis cases than its progenitor lineage has significantly increased virulence.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…GAs strains known to be highly pathogenic in mice and monkeys caused significantly lower survival and had significantly lower LD 50 s in wax worms than GAs strains associated with attenuated virulence or asymptomatic carriage. Furthermore, isogenic inactivation of proven virulence factors resulted in a significantly increased LD 50 and decreased lesion size compared to the wild-type strain, a finding that also strongly correlates with animal studies. Importantly, survival analysis and LD 50 determination in wax worms supported our hypothesis that a newly emerged GAs subclone that is epidemiologically associated with more human necrotizing fasciitis cases than its progenitor lineage has significantly increased virulence.…”
Section: Introductionsupporting
confidence: 63%
“…Results demonstrated that compared to subclone 5 strains, subclone 8 strains caused significantly lower survival over time (Fig. 5A) and have a significantly lower mean LD 50 (Fig. 5B).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 95%
See 2 more Smart Citations
“…These four genomes were sequenced to closure, and an average base call error rate of Ͻ1 in 10,000 (Q40) throughout. Four strains, MGAS12501-MGAS12504, are asymptomatic carriage isolates recovered in a population-based carrier study of recruits at Lackland Air Force Base (San Antonio, TX) (31). An additional eight strains were recovered from January 1, 1992 to December 31, 2003 in an ongoing prospective populationbased surveillance study of GAS invasive infections in Ontario, Canada (http:͞͞microbiology.mtsinai.on.ca͞research͞gas.shtml).…”
Section: Methodsmentioning
confidence: 99%